Agent-based computational models– a formal heuristic for institutionalist pattern modelling?. Issue 1 (15th June 2015) - GRÄBNER, CLAUDIUS
Abstract: I investigate the consistency of agent-based computational models with the institutionalist research program as outlined by Myrdal, Wilber and Harrison, Hodgson and others. In particular, I discuss whether such models can be a useful heuristic for 'pattern modelling': Can they provide a holistic, systemic and evolutionary perspective on the economy? How can agency be conceptualised within ABMs? Building on these issues, I discuss potentials and challenges of the application of ABM in institutionalist research. This discussion also relates to recent methodological advances in neo-Schumpeterian economics. I explain how institutionalists can benefit from these and suggest areas for joint research under the methodological umbrella of ABM.